2018
DOI: 10.37358/mp.18.4.5100
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Humic Acid Removal from Aqueous Systems by Using Polymeric Membrane Ultrafiltration Process

Abstract: This paper proposes to investigate in detail the behavior of polymeric membranes ultrafiltration process uses in the retention of humic acid from aqueous systems. Nowadays, the aqueous systems (contaminated water and/or wastewater) resulting from various domestic and industrial activities contain many contaminants, some of them increasingly dangerous to the environment. Laboratory testing of membranes in the ultrafiltration process as well as their experimentation with different chemical compounds is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…What leads to the decrease of the quality of the water both the surface and the underground are the different mining activities, industrial and municipal, the wastewater discharge, the improper storage of the different categories of waste. For a more efficient management of water quality it is necessary to monitor it regularly [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…What leads to the decrease of the quality of the water both the surface and the underground are the different mining activities, industrial and municipal, the wastewater discharge, the improper storage of the different categories of waste. For a more efficient management of water quality it is necessary to monitor it regularly [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…At the same time, 14 chemical elements present in the waste water were analyzed and after determining the concentration of the heavy metals after the completion of the experiment it can be confirmed that the use of polymeric membranes is and will be a viable solution for the purpose of protecting the environment and health.Industrial areas, regardless of the intensity of their activities, generate huge quantities of wastewater that contain pollutants from the most "friendly" with the environment to the most dangerous [1][2][3][4][5][6][7][8][9][10][11]. A quite important part of the industries generates waters that have in their composition high concentrations of heavy metals, such as: chromium, nickel, cadmium, manganese, iron, lead, etc., some being retained through the purification processes of the stations thus designed, others bypassing them, being a threat to aquatic life as well as to human health [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].In addition to the conventional methods of purification, the membrane technology has several advantages because the membranes, regardless of their type, have lower costs, are easier to exploit, in addition, they offer the possibility to separate the compounds for future use [29][30][31].The application of membranes in the processes of separation of heavy metals can have a rather high efficiency, but this efficiency depends very much on the working parameters of the experiment, such as the pH of the solution, the concentration of metals in the solution, the pressures that are created over time, other added solutions, operating time, etc. [32-34].Some studies have shown a decrease in the rejection of heavy metals as the pH value decreases, which meant a decrease in the absorption of metal ions [35]…”
mentioning
confidence: 99%
“…Industrial areas, regardless of the intensity of their activities, generate huge quantities of wastewater that contain pollutants from the most "friendly" with the environment to the most dangerous [1][2][3][4][5][6][7][8][9][10][11]. A quite important part of the industries generates waters that have in their composition high concentrations of heavy metals, such as: chromium, nickel, cadmium, manganese, iron, lead, etc., some being retained through the purification processes of the stations thus designed, others bypassing them, being a threat to aquatic life as well as to human health [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Filtration is a method of separating solid impurities from fluids, following flow through permeable porous media, called filter media or filters [8][9][10][11][12][13].…”
mentioning
confidence: 99%